1986
DOI: 10.1246/cl.1986.1615
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental Control of Photoinduced Electron Transfer and the Reverse Reactions in Porphyrin–Viologen Linked System

Abstract: Effects of spacer chain length on photoinduced electron transfer in porphyrin–viologen linked system (ZnPCnV) were investigated by laser photolysis. A long-living charge separated state was obtained with ZnPC4V in both homogeneous and bilayer systems, while ZnPC6V and ZnPC8V afforded appreciable charge separated states only in homogeneous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…8 Indeed, the transient absorption spectrum § after excitation at 337 nm coincides with that of 3 An (data not shown). According to these observations, it is concluded that excitation, either to MLCT or to 1 An, leads to 3 An.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…8 Indeed, the transient absorption spectrum § after excitation at 337 nm coincides with that of 3 An (data not shown). According to these observations, it is concluded that excitation, either to MLCT or to 1 An, leads to 3 An.…”
mentioning
confidence: 75%
“…2 Another approach would be to connect the components covalently and incorporate them into vesicles with a defined direction by rational design of the hydrophobic-hydrophilic balance. There are only a few reports on covalently linked chromophores in vesicles 3 in spite of the fact that the covalent approach has been met with great success in elucidating factors determining the rate of electron transfer in homogeneous solutions. 4,5 Here we report on vectorial processes effected by a covalently linked anthraceno-ruthenium complex 1 in dihexadecyl phosphate (DHP) vesicles.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Tetraarylporphyrins containing one to four viologen units have been extensively investigated. [1][2][3][4][5][6][7][8][9] The viologen units were found to act as fluorescence quenchers for the excited states of porphyrin, increasing the number of appended viologens led to more effective quenching. The influence of the solvent polarity, mutual orientation and separation distance between the electron donor and the electron acceptor, and types of spacer group on the rate of charge separation and charge recombination has been investigated by means of time-resolved fluorescence spectroscopy and ultrafast flash photolysis techniques.…”
Section: Introductionmentioning
confidence: 99%